Revisão taxonômica das espécies cisandinas de Mylossoma Eigenmann & Kennedy, 1903 (Characiformes: Serrasalmidae). - Mateussi, Nadayca Thayane Bonani (2015)
A review and a molecular analysis of the cis-Andean species of Mylossoma were carried out, comprising the analysis of 340 specimens, aiming to elucidate the recognition of Operational Taxonomic Units (OTUs) in cis-Andean Mylossoma and discuss species boundaries within the genus. Four valid species were recognized: M. aureum, distributed in the bacia do rio Amazonas; M. albiscopum, distributed in the bacias dos rios Amazonas e Orinoco; M. duriventre, distributed in the Paraguai, lower bacias dos rios Paraná and Uruguai; and M. unimaculatum, distributed in the bacias dos rios Tocantins-Araguaia. Mylossoma albiscopum and M. unimaculatum were removed from the synonymy of M. duriventre. The geographical distribution of M. duriventre was restricted to the Paraguai, lower bacias dos rios Paraná and Uruguai. An identification key, geographic distribution map and figures of all species are provided. Four OTUs were recognized based on both morphological and molecular approaches. The analysis using the GMYC with the model Birth-Death resulted in four OTUs, with M. duriventre being split in one unity in the Amazon, one in the Orinoco, one in Paraná-Paraguai and Tocantins-Araguaia which is coherent with our morphological results. The GMYC analysis using the model Yule indicated the existence of seven OTUs, in a way that M. duriventre was divided as two OTUs in the bacia do rio Amazon, two in the bacia do rio Orinoco, one in the bacias dos rios Paraná-Paraguai and one in the bacia dos rios Paraná-Paraguai. This disagreement between morphological and molecular approaches is discussed in the text.